The effect of GLP-1R agonists on the medical triad of obesity, diabetes, and cancer - Shahad Sabaawi Ibrahim (21842273) (2024)
Glucagon-like peptide-1 receptor (GLP-1R) agonists have garnered significant attention for their therapeutic potential in addressing the interconnected health challenges of diabetes, obesity, and cancer. The role of GLP-1R in type 2 diabetes mellitus (T2DM) is highlighted, emphasizing its pivotal contribution to glucose homeostasis, promoting β-cell proliferation, and facilitating insulin release. GLP-1R agonists have effectively managed obesity by reducing hunger, moderating food intake, and regulating body weight. Beyond diabetes and obesity, GLP-1R agonists exhibit a multifaceted impact on cancer progression across various malignancies. The mechanisms underlying these effects involve the modulation of signaling pathways associated with cell growth, survival, and metabolism. However, the current literature reveals a lack of in vivo studies on specific GLP-1R agonists such as semaglutide, necessitating further research to elucidate its precise mechanisms and effects, particularly in cancer. While other GLP-1R agonists have shown promising outcomes in mitigating cancer progression, the association between some GLP-1R agonists and an increased risk of cancer remains a topic requiring more profound investigation. This calls for more extensive research to unravel the intricate relationships between the GLP-1R agonist and different cancers, providing valuable insights for clinicians and researchers alike. Other Information Published in: Cancer and Metastasis Reviews License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s10555-024-10192-9